2017
DOI: 10.1183/13993003.01419-2016
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dyssynchrony and exercise capacity in idiopathic pulmonary arterial hypertension

Abstract: Survival in patients with pulmonary arterial hypertension (PAH) is determined by right ventricular (RV) function adaptation to afterload. How altered RV function impacts on exercise capacity in PAH is not exactly known.104 idiopathic PAH (IPAH) patients aged 52±14 years underwent a diagnostic right heart catheterisation, a comprehensive echocardiography including two-dimensional speckle tracking for RV dyssynchrony evaluation and a cardiopulmonary exercise test. Multivariate analyses were performed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…An increased RV-SD4 at rest has been previously reported to predict a decreased exercise capacity in severe PH (Badagliacca et al, 2017a) in relation to altered RV pump function (Badagliacca et al, 2015a;Kalogeropoulos et al, 2008). An increased RV-SD4 at rest has been previously reported to predict a decreased exercise capacity in severe PH (Badagliacca et al, 2017a) in relation to altered RV pump function (Badagliacca et al, 2015a;Kalogeropoulos et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…An increased RV-SD4 at rest has been previously reported to predict a decreased exercise capacity in severe PH (Badagliacca et al, 2017a) in relation to altered RV pump function (Badagliacca et al, 2015a;Kalogeropoulos et al, 2008). An increased RV-SD4 at rest has been previously reported to predict a decreased exercise capacity in severe PH (Badagliacca et al, 2017a) in relation to altered RV pump function (Badagliacca et al, 2015a;Kalogeropoulos et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Actually RV-SD4 may be higher than the upper limit of normal, taken as 20-22 ms, in no more than 50-60% of patients and stabilize around 27-30 ms in severe PH (Badagliacca et al, 2015a(Badagliacca et al, , 2015b(Badagliacca et al, , 2017a. Thus while RV-SD4 is correlated to RV function (Badagliacca et al, 2015a(Badagliacca et al, , 2015bKalogeropoulos et al, 2008;Lamia et al, 2017), functional state and exercise capacity (Badagliacca et al, 2015a(Badagliacca et al, , 2015b(Badagliacca et al, , 2017aKalogeropoulos et al, 2008;Meris et al, 2010), and survival (Badagliacca et al, 2015b), it has been found either to correlate but loosely or not at all with mPAP, PVR or pulmonary arterial compliance ( For other abbreviations, see Figure 1 TA B L E 3 Right ventricular dyssynchrony, pulmonary vascular resistance and mean pulmonary arterial pressure of study population excluding subjects with QRS >100 ms RV-SD4 (ms) 10 ± 4 1 2 ± 5 1 3 ± 6 1 3± 6 1 3± 5 1 2 ± 5 1 2 ± 4 mPAP, mean pulmonary artery pressure; PVR, pulmonary vascular resistance; RV-SD4, standard deviation of the times to peak systolic strain of the four mid and basal right ventricular segments; S pO 2 , percutaneous saturation of oxygen; WU, Wood units. * P < 0.05 vs. baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since exercise capacity of patients with precapillary PH is largely affected by the cardiac output, it is necessary to study the impact of RV contractile reserve on exercise capacity. In a study by Badagliacca et al, resting RHC parameters (cardiac index, right atrial pressure, and pulmonary arterial compliance), resting RVFAC, and right atrial area were shown to be independent predictors of peak VO 2 . However, little information is available on the association between RV function under stress conditions, especially RV contractile reserve with exercise capacity.…”
Section: Discussionmentioning
confidence: 91%